Shelf-life extension and quality improvement of a Portuguese traditional ready-to-eat meat product with vinegar - Laranjo, M. (2019)
Cabec a de xara is a traditional ready-to-eat meat product (RTEMP) from the Portuguese region of Alentejo. It is a moulded galantine made of low value pork pieces. The aim of this work was to test the addition of vinegar in reducing the spoilage microbiota, as well as controlling Listeria monocytogenes, in order to increase the shelf-life of cabec a de xara. Physicochemical (fatty acids and biogenic amines profiles), microbiological (mesophiles, psychrotrophic bacteria, enterobacteria, yeasts and L. monocytogenes) and sensory analyses were performed throughout the storage period. RTEMP vinegar samples always showed lower microbiological counts than control samples. Moreover, RTEMP vinegar samples showed significantly lower contents in vasoactive amines throughout the storage period, which might be explained by their significantly lower enterobacteria counts. Concerning sensory analysis, RTEMP vinegar samples generally scored higher in overall appreciation. Our results showed that shelf-life of cabec a de xara may be extended from 1 to 3 months.